Caring for chicks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Bob Akinwumi, who keeps layer hens, describes the feeding and disease control methods he uses in raising day old chicks.